The roots are (x + 1), (x - 4), (2 + 5i), and (2 - 5i).
g(x) = (x2 - 3x - 4)(x2 - 4x + 29)
Let us first consider x^2 - 3x - 4
By splitting the middle term
= x^2 + 1x - 4x - 4
= x(x + 1) - 4(x + 1)
= (x + 1)(x - 4)
Now let us consider x^2 - 4x + 29
First group the terms with variable on LHS and move the constant on the other side
x^2 - 4x = -29
Add 4 on both sides
x^2 - 4x + 4 = -29 + 4
x^2 - 4x + 4 = -25
It can be written as perfect squares
(x - 2)^2 = -25
We know that
i =√1
Take square root on both sides
x - 2 = ± 5i
x = 2 ± 5i
So we get,
x = 2 + 5i and x = 2 - 5i
g(x) = (x + 1)(x - 4)(2 + 5i)(2 - 5i)
A square root of a number is a price that, whilst extended by means of itself, offers variety. instance: four × four = 16, so a square root of 16 is four. The word that (−four) × (−four) = 16 too, so −four is likewise a square root of sixteen. The symbol is √ usually way the wonderful rectangular root. example: √36 = 6 (because 6 x 6 = 36).
Learn more about the square roots here https://brainly.com/question/3617398
#SPJ4